2021
DOI: 10.1039/d0na00617c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of small Ni-core–Au-shell catalytic nanoparticles on TiO2by galvanic replacement reaction

Abstract: Galvanic replacement reaction to synthesize small catalytic bimetallic Au–Ni nanoparticles with Ni core–Au shell structure directly on an oxide support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…Figure 8 displays the mutual overlap of three EDX elemental maps, Ni, Au and W. From the EDX image, it was indicated that Au and Ni elements were intermixed, showing gold NPs predominant with a good dispersion on the Ni surface near the support lattice. It can be concluded that the nickel NPs are incorporated in the gold matrix due to the metallic interaction between nickel and gold [ 46 , 47 , 48 ]. Metal–support interactions in the supported catalysts have been detected when the incorporation of metals into the framework of a support lattice occurs [ 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 8 displays the mutual overlap of three EDX elemental maps, Ni, Au and W. From the EDX image, it was indicated that Au and Ni elements were intermixed, showing gold NPs predominant with a good dispersion on the Ni surface near the support lattice. It can be concluded that the nickel NPs are incorporated in the gold matrix due to the metallic interaction between nickel and gold [ 46 , 47 , 48 ]. Metal–support interactions in the supported catalysts have been detected when the incorporation of metals into the framework of a support lattice occurs [ 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Essentially, reduced non-noble metal catalysts are utilized as metallic templates. As a result, structures with a noble-metal-rich shell and a non-noble-metal-rich core can be fabricated, providing the desired composition and properties for catalytic applications. , For example, Co@Pd core–shell NPs can be prepared by GRR between MOFs-derived Co NPs and Pd 2+ aqueous solution. The surface molar ratio of Pd/Co (0.21) was much higher than that in bulk (0.018), demonstrating the enrichment of noble metals on the surface through GRR method .…”
Section: Galvanic Replacement Of Metal Ions and Metal Substratementioning
confidence: 99%
“…Nanoalloys exhibit a broad array of chemical ordering patterns depending on the interaction between the constituent metals. Then, they are attractive from a fundamental perspective and often show distinct catalytic properties and stability as compared to individual metals, which is typically ascribed to the coupling effect and/or synergism in the electronic and/or geometric structures that occur when the metals are combined ( Ferrando et al, 2008 ; Tao, 2012 ; Yan et al, 2017 ; Ding et al, 2018 ; Añez et al, 2021 ; Reboul et al, 2021 ). Significant efforts have been put into the research field of nanocatalysis to explore the structure, surface composition, and atomic distribution for two metals systems, which are crucial for their properties and catalytic activities of bimetallic nanoalloys ( Ferrando et al, 2008 ; Jellinek, 2008 ; Piotrowski et al, 2012 ; Cui et al, 2013 ; Zhao et al, 2013 ; Guedes-Sobrinho et al, 2015 ; Gilroy et al, 2016 ; Wang et al, 2016 ; Wu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%